BEYOND LITERAL MEANINGS: EXPLORING COGNITIVE BARRIERS TO PHRASAL VERB MASTERY AMONG LANGUAGE LEARNERS - Jahaya, Nadira M.; Abu Sufian, Nazrin Afif; Nasaruddin, Dina Mardhiana (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Phrasal verbs, as essential components of English communication, pose significant cognitive barriers for second language (L2) learners due to their semantic opacity, syntactic variability, and contextual dependency. Despite their prevalence in both spoken and written discourse, the mastery of phrasal verbs remains a persistent challenge, hindering learners’ communicative competence and fluency. This study aims to explore the cognitive barriers that impede phrasal verb acquisition and propose a comprehensive conceptual framework to address these challenges. Through an extensive review of existing literature, key insights from cognitive linguistics, second language acquisition (SLA) theories, and vocabulary learning models were synthesized to highlight gaps in current research. Findings reveal that learners struggle with decoding figurative meanings, navigating syntactic rules, and applying phrasal verbs appropriately in context. Cross-linguistic interference, limited exposure, and individual differences further exacerbate these difficulties. The proposed framework integrates cognitive processes such as noticing patterns, input processing, and conceptual mapping to bridge the gap between input exposure and mastery. It emphasizes the need for explicit instruction, contextualized practice, and technological innovations like AI-driven adaptive learning tools. The implications of this study extend to both theory and practice, offering educators and policymakers actionable strategies to enhance L2 vocabulary instruction. By fostering interdisciplinary collaboration among academicians, policymakers, and industries, this research paves the way for innovative solutions to empower learners in overcoming the complexities of phrasal verbs. Future research should prioritize longitudinal studies and cross-disciplinary approaches to advance understanding and instructional practices.